2014
DOI: 10.1177/1090820x14530552
|View full text |Cite
|
Sign up to set email alerts
|

Transaxillary Nonendoscopic Subpectoral Augmentation Mammaplasty: A 10-Year Experience With Gel vs Saline in 2000 Patients—With Long-Term Patient Satisfaction Measured by the BREAST-Q

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 26 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…4,19 In augmentation patients, Gryskiewicz et al demonstrated that patients who received silicone implants were more satisfied with their overall outcome than patients who received saline. 20 In breast reconstruction patients, multiple studies have demonstrated similar findings with higher overall satisfaction, psychological well-being, sexual well-being, physical function, and satisfaction with their surgeon in patients receiving silicone implants in comparison to saline. 2023 The BREAST-Q has been instrumental in helping to demonstrate greater patient satisfaction with silicone implants compared to saline, providing essential information to help future patients make educated decisions about reconstructive options.…”
Section: Discussionmentioning
confidence: 85%
“…4,19 In augmentation patients, Gryskiewicz et al demonstrated that patients who received silicone implants were more satisfied with their overall outcome than patients who received saline. 20 In breast reconstruction patients, multiple studies have demonstrated similar findings with higher overall satisfaction, psychological well-being, sexual well-being, physical function, and satisfaction with their surgeon in patients receiving silicone implants in comparison to saline. 2023 The BREAST-Q has been instrumental in helping to demonstrate greater patient satisfaction with silicone implants compared to saline, providing essential information to help future patients make educated decisions about reconstructive options.…”
Section: Discussionmentioning
confidence: 85%
“…Additionally, in implant-based reconstruction, the BREAST-Q has been used to demonstrate superior PRO scores when using silicone in comparison to saline implants for reconstructive as well as cosmetic augmentation purposes (35-38). …”
Section: Discussionmentioning
confidence: 99%
“…The lack of a significant association of type of implant texture with implant malposition may be attributed to the small sample size per group, which may not be large enough to detect a given difference as significant. Low rates of malposition of 0.4 21 and 1.2% 20 have been reported in studies on subpectoral breast augmentation. According to Maxwell et al, 5 macrotextured implants are associated with low rates of malposition, as their texture promotes adhesion of the implant to the surrounding tissue.…”
Section: Discussionmentioning
confidence: 93%